Girolamo Fracastoro – renesansowy uczeń Wergiliusza (Girolamo Fracastoro – a Renaissance Vergil’s Disciple) - Sapota, Tomasz (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2025)
Girolamo Fracastoro (1476/78–1553), an Italian scholar, physician, and poet, has been celebrated throughout the ages as the author of Syphilis sive morbus Gallicus, a hexametric poem discussing the symptoms and the origin of the epitomical venereal disease. The term was modelled on one of the poem’s fictional characters, a pastor called Syphilus. Although Fracastoro was profoundly influenced by Lucretius’ rendition of the Democritus and Epicure’s theory of the world, which can be traced in similes, he undoubtedly regarded Vergil as the ultimate paragon of poetic accomplishment. This text explains how Fracastoro tried to emulate the hallowed oeuvre of his great predecessor.